2017
DOI: 10.1021/acs.jafc.7b00715
|View full text |Cite
|
Sign up to set email alerts
|

Mycochemical Changes Induced by Selenium Enrichment in P. ostreatus Fruiting Bodies

Abstract: The effects of selenium enrichment on the biological efficiency, phenolic compounds, amino acid profile, antioxidant capacity, and cellular antioxidant activity (CAA) were evaluated in Pleurotus ostreatus fruiting bodies (FB) harvested during three sequential flushes. Sodium selenate was used to reach selenium content of 17.5 or 5.8 mg/kg in the sorghum straw substrate. Biological efficiency and total selenium content increased. One of the main differences among treatments was in ergothioneine content, an indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
(92 reference statements)
2
12
0
Order By: Relevance
“…Particularly in a strain of P. ostreatus, bound coumaric and ferulic acids were found at the levels of 556 and 90 µg per 100 g d.w., respectively. 72 The presence of phenolic acids in the Pleurotus genus was confirmed in other studies with P. ostreatus, P. eryngii and P. sajor-caju. [73][74][75] Some authors have identified the presence of flavonoids in Pleurotus spp.…”
Section: Phenolic Compoundssupporting
confidence: 64%
“…Particularly in a strain of P. ostreatus, bound coumaric and ferulic acids were found at the levels of 556 and 90 µg per 100 g d.w., respectively. 72 The presence of phenolic acids in the Pleurotus genus was confirmed in other studies with P. ostreatus, P. eryngii and P. sajor-caju. [73][74][75] Some authors have identified the presence of flavonoids in Pleurotus spp.…”
Section: Phenolic Compoundssupporting
confidence: 64%
“…Moreover, zinc and, in a lesser degree, selenium supplementation positively affected gallic acid content in P. eryngii mycelium, while this acid was not detected in fruiting bodies. According to Carrasco-Gonzalez et al [21], coumaric and ferulic acid contents in P. ostreatus fruiting bodies were positively affected through Se biofortification.…”
Section: Organic Compound-total Phenolics Lovastatin and Dpph • Scamentioning
confidence: 98%
“…Gallic acid is known to activate diverse pharmacological and biochemical effects in humans including strong anti-cancer, antioxidant, and anti-inflammatory factors [20]. In addition, it elevated the levels of enzymatic and nonenzymatic antioxidants [21]. Pleurotus eryngii is a significant source of lovastatin, also known as monocline k, which is a naturally occurring compound, and the hypolipidemic agent acts through the inhibition of the HMG-CoA reductase [22].…”
Section: Introductionmentioning
confidence: 99%
“…A 36 kDa Se‐containing protein isolated and purified from Ganoderma lucidum , that contained 3 times more Se than its crude form, showed 3 times the radical‐scavenging activity as compared to the crude form, demonstrating that the increasing antioxidant property of this protein depended quantitatively on its Se content (Du, Zhao, Li, Zhao, & Hu, ). Carrasco‐Gonzalez, Serna‐Saldívar, and Gutierrez‐Uribe () reported increase in total antioxidant power of P. ostreatus was associated with increase in Se content.…”
Section: Resultsmentioning
confidence: 99%